Efektivitas Pengawasan Keuangan Publik dalam Mewujudkan Transparansi Apbd di Kabupaten Magetan - Aditya Bagus Pratama; Rayhan Adi Wicaksono; Revienda Anita Fitrie; Eva Hany Fanida (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Public financial oversight is a key instrument in ensuring transparency in the management of the Regional Revenue and Expenditure Budget (APBD). This study aims to analyse the effectiveness of public financial oversight in supporting APBD transparency in Magetan Regency. The study employs a descriptive qualitative approach, utilising secondary data collected through the review and analysis of official local government documents, financial reports, relevant regulations, and pertinent academic journals. The data were analysed using content analysis techniques to examine financial oversight practices and their openness to the public. The results indicate that public financial oversight in Magetan Regency has been relatively effective, as evidenced by the attainment of an Unqualified Opinion (WTP) from the State Audit Agency for three consecutive years during the 2021–2023 period. Nevertheless, the transparency of the APBD has not yet been fully optimised due to the limited publication of budget documents, low public participation in the planning process, and the underutilisation of information technology in the dissemination of budget information. These findings indicate that the strengthening of transparency aspects needs to be carried out continuously so that public financial oversight can have a more tangible impact on the accountability of APBD management